A bispecific transmembrane antibody simultaneously targeting intra‐ and extracellular epitopes of the epidermal growth factor receptor inhibits receptor activation and tumor cell growth. Issue 11 (18th November 2013) - Müller, Nina; Hartmann, Cord; Genßler, Sabrina; Koch, Joachim; Kinner, Andrea; Grez, Manuel; Wels, Winfried S.
<x xml:space="preserve">Abstract</x> Epidermal growth factor receptor (EGFR) plays an important role in essential cellular processes such as proliferation, survival and migration. Aberrant activation of EGFR is frequently found in human cancers of various origins and has been implicated in cancer pathogenesis. The therapeutic antibody cetuximab (Erbitux) inhibits tumor growth by binding to the extracellular domain of EGFR, thereby preventing ligand binding and receptor activation. This activity is shared by the single chain antibody fragment scFv(225) that contains the same antigen binding domain. The unrelated EGFR‐specific antibody fragment scFv(30) binds to the intracellular domain of the receptor and retains antigen binding upon expression as an intrabody in the reducing environment of the cytosol. Here, we used scFv(225) and scFv(30) domains to generate a novel type of bispecific transmembrane antibody termed 225.TM.30, that simultaneously targets intra‐ and extracellular EGFR epitopes. Bispecific 225.TM.30 and related membrane‐anchored monospecific 225.TM and TM.30 proteins carrying extracellular scFv(225) or intracellular scFv(30) antibody fragments linked to a transmembrane domain were expressed in EGFR‐overexpressing tumor cells using a doxycycline‐inducible retroviral system. Induced expression of 225.TM.30 and 225.TM, but not TM.30 reduced EGFR surface levels and ligand‐induced EGFR activation, while all three molecules markedly inhibited tumor cell growth. Co‐localization of 225.TM with EGFR was predominantly found on the cell surface, while interaction with 225.TM.30 and TM.30 proteins resulted in the redistribution of EGFR to perinuclear compartments. Our data demonstrate functionality of this novel type of membrane‐anchored intrabodies in tumor cells and suggest distinct modes of action of mono‐ and bispecific variants.